Ecological Knowledge and Attitudes: Between Lived Experience, School and Socio-digital Networks - Limachi Pérez, Vicente (2025)
The article describes the influences of family, school, and sociodigital networks on the construction of environmental awareness among secondary school students in urban and rural schools in the department of Cochabamba, Bolivia. Using a mixed-methods approach—combining surveys, observations, and interviews—data were collected on the environmental knowledge and attitudes of students in three schools. The results revealed that students' environmental concerns vary depending on their surroundings: air pollution in urban areas, water scarcity and contamination in rural Andean regions, and forest fires in the tropical region. Students prioritize the internet (especially Google, YouTube, and TikTok) as their main source of information on environmental issues at the local, national, and global levels. Their reliance on these sources is linked to the speed and multimodal formats they offer. Visual content such as photos, videos, and infographics shapes their perceptions and emotions regarding issues like animal abuse and species extinction. Despite isolated initiatives such as school gardens or orchards, schools do not effectively integrate environmental education into the curriculum, which limits its formative impact. In conclusion, the article highlights the need to strengthen the role of formal education, based on the interaction between family, school, and sociodigital networks, to enhance learning and awareness on ecological issues. It advocates leveraging the potential of sociodigital networks to foster critical awareness and bridge the gap between acquired knowledge and pro-environmental practices, in order to move toward a sustainable relationship with the environment.